Orally peppermint oil in small bowel capsule endoscopy: Novel approach to improve completion rates in patients at risk of delayed gastric transit - O'Hara, Fintan John; Costigan, Conor; Mc Namara, Deirdre (Endoscopy International Open, 2025)
Small bowel capsule endoscopy (SBCE) is crucial in diagnosing small bowel diseases, yet incomplete examinations often result from prolonged gastric transit time. This study aimed to assess the efficacy of orally administered peppermint oil solution as a prokinetic agent to improve SBCE completion rates in patients with delayed gastric transit risk factors.Conducted as a single-center, prospective, open-label, non-inferiority trial, the study involved 132 patients identified as at risk for delayed gastric transit. Participants were divided into three groups: peppermint oil solution group (n = 57), real-time monitoring and intravenous prokinetics group (n = 75), and control group without risk factors (n = 193). Primary outcomes included SBCE completion rates, gastric transit time (GTT), small bowel transit time (SBTT), diagnostic yield, and bowel preparation quality.Completion rates were high and comparable among groups, with 94.7% in the peppermint group, 90.7% in the real-time monitoring group, and 95.3% in the control group. The peppermint group exhibited a significantly shorter mean GTT of 42.3 minutes compared with 57.0 minutes in the real-time monitoring group (P = 0.0423). However, SBTT was longer in the peppermint group at 246 minutes versus 193 minutes in the real-time monitoring group (P = 0.0081), although similar to the control group at 228.3 minutes (P = 0.2612). Diagnostic yield and bowel preparation quality were consistent across all groups.Oral peppermint oil solution is a safe and effective alternative to traditional prokinetics, enhancing SBCE completion rates while reducing time and resource use in the endoscopy unit.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Endoscopy Upper GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE)